Longitudinal Ultrasound-Guided Injection Curriculum for Physical Medicine and Rehabilitation Residents. (23rd May 2023) - Eventov, Michelle; Bean, Allison C.; D'Amico, Ella; Fultz, Connor; Cerana, Kerry; Helkowski, Wendy; Schroeder, Allison N.
Abstract: Physiatrists are increasingly using musculoskeletal ultrasound for both diagnostic and therapeutic purposes. However, a standardized longitudinal curriculum for instructing physical medicine and rehabilitation residents in performing ultrasound-guided interventional procedures has yet to be established. The purpose of this study is to develop and assess the effectiveness of a longitudinal curriculum in training residents to perform common ultrasound-guided musculoskeletal injections using fresh-frozen cadaveric specimens. The course included six weekly hands-on educational sessions, divided by anatomical region, integrated into an established anatomy and physical examination curriculum. After completion of the curriculum, residents reported improved comfort and confidence and displayed improved competence in performing these injections. Other physiatry residency programs should consider implementing longitudinal, hands-on cadaveric training courses to better prepare trainees to perform ultrasound-guided injections as part of their future clinical practice.